(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The behavioral and psychological symptoms of Alzheimer’s disease impose a significant burden on the patients family and caregiver. Objectives: The purpose of this study was to assess the health of individuals who care for Alzheimers patients by using the World Health Organization Quality of Life Questionnaire (WHOQoL-Bref) and the Caregiver Stress Scale, and also to evaluate the relationship between the health and demographic data of these caregivers.